2003
DOI: 10.1002/aheh.200300501
|View full text |Cite
|
Sign up to set email alerts
|

Depth Distribution of Chlorinated and Polycyclic Aromatic Hydrocarbons in Floodplain Soils of the River

Abstract: Depth profiles of various organic micropollutants were measured in floodplain soils of the river Elbe, Germany. The study area lies in the former East Germany (GDR) and displays elevated concentrations of pesticides and polycyclic aromatic hydrocarbons. Depth distributions were found to vary at different sampling points and among the individual compounds, which could only partly be explained by comparing normalized concentrations (organic carbon). Metabolization, mobilization, and effects of sedimentation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 10 publications
2
10
0
Order By: Relevance
“…The DDX concentrations of the samples Ry 2 to 4 were similar to the DDX concentrations of the German Elbe (Witter et al 1998), Czech Elbe and Morava and Russian Yachroma River, but were lower than the German Elbe (Witter et al 2003) and Spittelwasser River floodplain soils. The HCB concentrations of this study were comparable to the Czech Elbe and Dřevnice River floodplain soils, but two orders of magnitude lower than the concentrations in the floodplain soils of the German Elbe (Witter et al 1998(Witter et al , 2003. The methoxychlor concentrations in the Oka River floodplain soils were higher by a factor of 5 compared with the German Elbe River floodplain soils.…”
Section: Concentrations Of Popssupporting
confidence: 51%
See 2 more Smart Citations
“…The DDX concentrations of the samples Ry 2 to 4 were similar to the DDX concentrations of the German Elbe (Witter et al 1998), Czech Elbe and Morava and Russian Yachroma River, but were lower than the German Elbe (Witter et al 2003) and Spittelwasser River floodplain soils. The HCB concentrations of this study were comparable to the Czech Elbe and Dřevnice River floodplain soils, but two orders of magnitude lower than the concentrations in the floodplain soils of the German Elbe (Witter et al 1998(Witter et al , 2003. The methoxychlor concentrations in the Oka River floodplain soils were higher by a factor of 5 compared with the German Elbe River floodplain soils.…”
Section: Concentrations Of Popssupporting
confidence: 51%
“…The contamination of the Oka River catchment with PCBs was in the same order of magnitude as the Czech Morava and Elbe River floodplain soils, but only the sample Ry 2 was comparable to the data from the German Elbe River (Witter et al 1998). The floodplain soils of the German Elbe (Witter et al 2003), the Czech Dřevnice and the Russian Yachroma River were more highly contaminated than the Russian Oka River floodplain soils. The comparison of the cyclodien concentrations with data published by Witter et al (1998) for the German Elbe floodplains soils showed a similar range of contamination.…”
Section: Concentrations Of Popsmentioning
confidence: 50%
See 1 more Smart Citation
“…Regarding b-HCH deposits, Witter et al [14,15] showed that the b-HCH isomer was the dominant hexachlorocyclohexane compound in alluvial soils of the Middle Elbe. The samples of six depth profiles between river km 435 and 440 [14] were taken in 1997.…”
Section: Anthropogenic and Geogenic Tracers 2331 B-hch (Hexachloromentioning
confidence: 99%
“…The samples of six depth profiles between river km 435 and 440 [14] were taken in 1997. Consequently a maximum calculation period of 47 years can be assumed.…”
Section: Anthropogenic and Geogenic Tracers 2331 B-hch (Hexachloromentioning
confidence: 99%